Overview of the Indian Corporate Sector : 1989-2002 - Topalova, Petia (IMF Working Papers; Working Paper ;, 2004)
This paper uses firm-level data to examine the performance of India's nonfinancial corporate sector since 1989 and evaluate its financial vulnerabilities. While promising trends in liquidity, profitability, and leverage of the sector emerged in the early 1990s, they experienced a reversal after 1996. Nonetheless, most indicators were still at comfortable levels, and there is evidence of improvement in 2002, the last year in our sample. However, a number of firms still face problems servicing their debt obligations, posing a risk to lenders. In particular, the aggregate interest coverage of the corporate sector indicates that potential nonperforming loans of the corporate sector remain high. This underscores the need for close monitoring of the corporate sector in the future.